EU action in support of civil society in Asia (Destined to Cooperate? Various Dimensions of European Union Policy Towards Asian Countries, 2024)
The European Union actively promotes the engagement of civil society in shaping policies on a global scale. Civil society, founded on democratic principles, freedom of belief, and association, constitutes a crucial element of international cooperation. This chapter examines EU actions in support of civil society, with a particular focus on Asia. Analyzing EU strategies and activities towards civil society in the Asian region allows to address questions regarding the nature of EU support, its core values, and priority areas. This chapter facilitates understanding of the EU's role in promoting and strengthening civil society internationally, especially in Asian countries. This chapter also serves as an introduction to the third part of the book, which presents examples of EU action on civil society in three different Asian countries.